Free or a Servant?. Issue 1 (2nd January 2017) - Schlink, Bernhard
Abstract: In 1858, the German poet-jurist Theodor Storm wrote a small poem that keeps intriguing interpreters: "One man enquires: And then what? / The other, merely: Is it right? / And so, observing, we can spot / The free man – and the servant's plight." Who is the free man – the one who merely asks whether something is right or the one who accepts responsibility for the consequences of his actions? Who is the servant – the one who fearfully allows his actions to be determined by their advantages and disadvantages or the one who does what his master says is right? The article asks what Theodor Storm meant, and what is actually correct.